International Students and Their Accommodation Choices: Evidence from Eastern Mediterranean University - Awa, Emmerentia Wozwi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
The choices made by international students when they travel for studies abroad regarding their accommodation has become of increasing importance. This study empirically explores the choices made by International students regarding their accommodation in the city of Famagusta, Turkish Republic of North Cyprus. The increasing influx of International students into Famagusta, Turkish Republic of North Cyprus has a significant impact on the house rent prices and the construction of more dormitories and apartment in the city of Famagusta. The analysis reveals that most of the International students prefer accommodations that are affordable, well furnished, having AC provision and a WIFI connection. This thesis empirically investigates on the factors which influence the choices of International students in deciding on the accommodation they live in. The T –test showed that there are a significant difference among EMU students based on gender, age and Nationalities when it comes to the choices they make regarding where they live in Famagusta TRNC. Keywords: EMU students, type of accommodation, Affordability, nearness to the University, rental Prices, frequency tables, t-test.

Öz: Son yıllarda uluslararası öğrencilerin gittikleri ülkelerde yaptıkları barınak seçeneklerinin önemi artarak devam etmektedir. Bu çalışma uluslararası öğrencilerin Kuzey Kıbrıs’ın, Mağusa şehrinde yeralan Doğu Akdeniz Üniversitesindeki barınak seçeneklerini ampirik bağlamda araştırmaktadır. Üniversiteye olan öğrenci yoğunluğundan dolayı, yurt ve apartman yapımlarında, bunlara bağlı kiralarda büyük bir etki hasıl olmuştur. Çalışma sonuçları öğrencilerin yurt ve barınak seçeneklerinde iyi döşenmiş, klimalı ve kablosuz internet imkanları olmasına dikkat ederler. Bağımsız ti-test ve kullanılarak yapılan bu çalışmada Doğu Akdeniz üniversitesi öğrencilerinin yurt ve barınak seçeneklerinde cinsiyet, yaş ve ulusal bağlamda anlamlı farklılıklar bulunmuştur. Anahtar kelimeler: Doğu Akdeniz üniversitesi, yurt çeşidi, maddi yeterlilik, bağımsız ti-test.
Master of Arts in Marketing Management. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2016. Supervisor: Prof. Dr. Sami Fethi.
Keywords: Business Administration; Marketing Management; EMU students; type of accommodation; Affordability; nearness to the University; rental Prices; frequency tables; t-test